Financial Determinants of Tax Avoidance: The Moderating Role of Firm Size - Ilmi, Ainun Analisa; Wafiroh, Novi Lailiyul (Universitas Pendidikan Nasional, 2025)
This study aims to examine the effect of profitability, capital intensity, and leverage on tax avoidance with company size as a moderating variable in food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) survived 2019-2023. The research method used is panel data regression with a quantitative approach using Eviews 12 software. The results showed that profitability has a negative and significat effect on tax avoidance, which means that increasing profitability reduces the level of tax avoidance. Capital intensity has a significant effect on tax avoidance, where companies with high fixed asstes tend to avoid taxes through asset depreciation. However, leverage does not have a significant effect on tax avoidance, indicating that the use of debt by companies is more focused on operational funding than tax avoidance strategies. In a moderating role, company size does not strengthen the relationship between profitability and tax avoidance or leverage and tax avoidance. However, company size is able to strengthen the relationship between capital intensity and tax avoidance, indicating that companies with large assets are better able to optimize tax strategies. These findings provide insights for regulators in understanding the factors that influence tax avoidance and its implications fot tax policy. The limitations of this study only use manufacturing companies in the food and beverage sector.